Morbilidad bucal percibida y características sociales en la población desplazada y destechada de un asentamiento del municipio de Bello (Antioquia), 2005 (2006)
ABSTRACT: Forceful displacement due to violence is one of the social phenomena with most relevance in public health, due to its relationship with social conditions and with the determinants that affect the health situation. Oral health is not strange to his situation, therefore, it is necessary to study what is happening with specific group populations. A descriptive study was carried out in a group of displaced and homeless population in which several social demographic variables were identified, as well as the perception of oral morbidity and their use of services related to it. Deficient life conditions were found, such us unemployment, lack of educational opportunities, financial hardships, difficulty of access to health services, high perception or oral and dental morbidity and a lack of knowledge of their health rights. It is mandatory to advance in the construction of proposals of intervention within specific parameters, keeping in mind that quality of life and welfare are fundamental axis of dignified life and of total health.